The Orphic Argonautica - Tatiana Alexandrova (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ)
The publication presents a literary translation of the late Antique poem “Orphic Argonautica”, approximately dating from the 4th –5th centuries AD. This is a pseudepigraph, the author of which deliberately hid his name by signing the poem with the name of the mythical singer Orpheus. Along with the “Lithica”, the “Orphic Argonautica” is one of the two epic poems included in the corpus of orphic texts. From other versions of the epic on the plot of the myth about the Argonauts, it differs in length, being shorter, and in the special emphasis on the role of the ‘author’ and narrator, Orpheus; with attention to the sacred rites that he performs and with the description of the path itself. The love story of Jason and Medea, unlike other poems, is consigned to the periphery. In addition to the predictable coincidences with the “Argonautica”by Apollonius of Rhodes, in the “Orphic Argonautica” some intersections can be seen with the Latin epic poems: “Argonautica”: by Valerius Flaccus and “Punica”: by Silius Italicus, although the author can be not familiar with them he uses the same sources. The second part of the poem is of the greatest interest, in which the periplus of Northern Europe is given. The author follows the version of Timaeus from Tauromenium (4th century BC), according to which the Argonauts returned from Colchis through the Tanais, northern rivers and Ocean, and, having rounded Western Europe, entered the Mediterranean Sea. At the same time, he uses other geographical sources of Hellenistic time, thanks to which the narrative is basically plausible and testifies to the acquaintance of the Greeks with the northern sea routes. The literary merits of the poem are traditionally underestimated by scholars, but such an assessment is largely biased: the author pursues his own goals and chooses literary means in relation to them.